DETERMINANTS OF POLISH AGRO-FOOD SECTOR COMPETITIVENESS – THE ROLE OF TOURISM DEMAND - Sawicka, Janina (Acta Scientiarum Polonorum. Oeconomia, 2010)
Valuable features of rural areas concerning natural environment, culture and landscape have been also used for tourism development purposes. In Poland they have still been underestimated, especially in peripheral areas, borderland, despite their uniqueness and diversity on the European and international scale. Poland has become an inherent part of the European model of rural and agricultural development, by its multifunctionality and multidirectional character. In the non-agricultural functions competitiveness advantages should be sought. Revenues generated by tourism and agrotourism are essential source of inhabitants’ income, having impact on regional economy development. Along with tourism and agrotourism development consumption is growing, especially consumption of traditional and locally made food.